Exploring the writing attainment gap: profiling writing challenges and predictors for children with English as an additional language - Booton, SA; Menon, P; Kyriacou, M; Murphy, VA (Springer, 2024)
While there is some evidence of a gap in English writing achievement between children with English as an additional language (EAL) compared to their monolingual English-speaking (EL1) peers, the source of this gap remains unclear. This study examines whether writing presents a specific challenge for children with EAL beyond their oral language and reading skills, and whether the factors affecting writing skills differ between EAL and EL1 groups. In a longitudinal design, 100 children aged 9 to 10 years completed a fiction writing task and single-word spelling task twice over a school year. They also completed a non-fiction writing task, and measures of nonverbal intelligence, receptive vocabulary, expressive and receptive oral language, decoding, and reading comprehension. Children with EAL demonstrated lower general writing performance than monolinguals, commensurate with their other language and reading skills, but a relative strength in single-word spelling. Predictors were similar for children with EAL and monolinguals, with decoding skill predicting spelling and writing, and expressive oral language predicting writing. Effects of genre and specific writing sub-skills are also discussed, as well as implications for closing the writing attainment gap.